2023
DOI: 10.1002/jcp.31010
|View full text |Cite
|
Sign up to set email alerts
|

Neuro death through autophagy via the acetylation of FoxO1 by SIRT2 in the hippocampus of mice in a autism spectrum disorder mice model

Abstract: Autism Spectrum Disorder (ASD) is a series of complex neurodevelopmental disorders, which can affect children's social, behavioral and communication abilities. A member of the Sirtuins family of NAD + dependent deacetylases called SIRT2 could regulate the inflammation progress during stress, but the relevant mechanism has not been clearly defined. In the present study, the ASD model of wild type and SIRT2 knock out mice was established to evaluate the impact on the homeostasis of neurons in the hippocampus usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this regard Arutiunian et al, reported that reduced in grey matter volume of hippocampus is linked with the severity of ASD symptoms in children ( Arutiunian et al, 2023 ). Furthermore various studies have demonstrated role of neural and signaling alterations of the hippocampus in the pathophysiology of ASD ( Dutra et al, 2023 , Zohny et al, 2023 , Guo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard Arutiunian et al, reported that reduced in grey matter volume of hippocampus is linked with the severity of ASD symptoms in children ( Arutiunian et al, 2023 ). Furthermore various studies have demonstrated role of neural and signaling alterations of the hippocampus in the pathophysiology of ASD ( Dutra et al, 2023 , Zohny et al, 2023 , Guo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%